Suitability of Duckweed (Lemna minor) as Feed for Fish in Polyculture System (International Journal of Agricultural Research, Innovation and Technology, 2013)
In the present study, we conducted an experiment to evaluate the effects of duckweed (Lemna minor) as feed on fish production in polyculture. The experiment had 2 treatments where in treatment 1 (T1) ponds were supplied with duckweed as feed and in treatment 2 (T2) ponds were kept as control (without supply of duckweed). Average survival rates in T1 and T2 were 90 and 89%, respectively. The specific growth rates (SGR) were higher in T1. Calculated net production in T1 was 6.25 tons ha.-1 yr.-1 and in T2 was 2.84 tons ha.-1 yr.-1. The ranges of physico-chemical parameters analyzed were within the productive limit and more or less similar in all the ponds under both treatments during the experimental period. There were 24 genera of phytoplankton under 5 major groups and 10 genera of zooplankton under 3 major groups found in the experimental ponds. The net production in T1 was significantly higher than that of T2 indicated the use of duckweed as feed for fishes is economically sustainable in polyculture. DOI: http://dx.doi.org/10.3329/ijarit.v2i1.13994 Int. J. Agril. Res. Innov. & Tech. 2 (1): 42-46, June, 2012